Răspuns :
2*(18-12x+36) - 9 = 3*(19-10x+15)-21
36-24x+72-9 = 57-30x+45-21
-24x+30x = 57+45-21-36-72+9
6x = 102-21-36-72+9
6x = 81-36-72+9
6x = 45-72+9
6x = -27+9
6x = -18
x = -18:6
x = -3
36-24x+72-9 = 57-30x+45-21
-24x+30x = 57+45-21-36-72+9
6x = 102-21-36-72+9
6x = 81-36-72+9
6x = 45-72+9
6x = -27+9
6x = -18
x = -18:6
x = -3
rezolvare:
2x(18-12x+36)-9=3x(19-10x+15)-21
36-24x+72-9=57-30x+45-21
-24x+30x=57+45-21+9-72-36
6x=-18
x=-3
2x(18-12x+36)-9=3x(19-10x+15)-21
36-24x+72-9=57-30x+45-21
-24x+30x=57+45-21+9-72-36
6x=-18
x=-3